2022
DOI: 10.3390/molecules27196425
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Kalanchoe pinnata as a Cancer Treatment Adjuvant and an Epigenetic Regulator

Abstract: Cancer is a global public health problem that is related to different environmental and lifestyle factors. Although the combination of screening, prevention, and treatment of cancer has resulted in increased patient survival, conventional treatments sometimes have therapeutic limitations such as resistance to drugs or severe side effects. Oriental culture includes herbal medicine as a complementary therapy in combination with chemotherapy or radiotherapy. This study aimed to identify the bioactive ingredients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…The EE of K. pinnata showed the highest cytotoxicity against a lymphoma cell line, in a dose-dependent manner [ 135 ]. The anticancer mechanisms were revealed through a molecular approach [ 167 ] to support the use of K. pinnata as an adjuvant in cancer treatment. Gallic acid, caffeic acid, coumaric acid, quercetin, quercitrin, isorhamnetin, kaempferol, bersaldegenin, bryophyllin A, bryophyllin C, bryophynol, bryophyllol, bryophollone, stigmasterol, and campesterol were identified as bioactive compounds which participate.…”
Section: Resultsmentioning
confidence: 99%
“…The EE of K. pinnata showed the highest cytotoxicity against a lymphoma cell line, in a dose-dependent manner [ 135 ]. The anticancer mechanisms were revealed through a molecular approach [ 167 ] to support the use of K. pinnata as an adjuvant in cancer treatment. Gallic acid, caffeic acid, coumaric acid, quercetin, quercitrin, isorhamnetin, kaempferol, bersaldegenin, bryophyllin A, bryophyllin C, bryophynol, bryophyllol, bryophollone, stigmasterol, and campesterol were identified as bioactive compounds which participate.…”
Section: Resultsmentioning
confidence: 99%
“…Others include quercitrin, quercetin, kaempferol, and rutin. The hepatoprotective benefits of afzelin, derived from Kalanchoe pinnata , have been demonstrated, indicating its potential to mitigate liver damage induced by carbon tetrachloride [ 39 , 40 , 41 , 42 ].…”
Section: Sources and Pharmacological Profile Of Afzelinmentioning
confidence: 99%
“…An increasing number of studies support the anti-tumor effects of herbal medicines as epigenetic modification modulators, including turmeric, tannin, yam and Kalanchoe pinnata ( 107 ), which can target DNA (cytosine-5-)-methyltransferase 1 to inhibit P65 gene methylation and interfere with CRC cell infiltration and migration ( 108 ). Although the relationship between Chinese medicine and m6A methylation has not yet been fully elucidated, some studies have found that herbal extracts can regulate DNA methylation, including chaihu saponin ( 109 ), quercetin ( 110 ) and catechins ( 111 ).…”
Section: Therapeutic Exploration Of Targeting Key M6a Methylation Enz...mentioning
confidence: 99%